2001
DOI: 10.1238/physica.regular.063a00181
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Energy Levels in Odd-Mass Copper Nuclei by Means of the (α,p) Reaction

Abstract: A linear initial-value code is used to study the combined effect of resistivity and viscosity on the stability of a static z-pinch. Resistivity alone is seen to have only a minor effect, even at Lundquist parameters for which neglecting the evolution of the equilibrium is unjustified. However, the introduction of a scalar viscosity leads to strong damping of m = 0 and m = 1 modes, and can completely stabilize short-wavelength perturbations. In agreement with SPIES (1988, Plasma Phys. Contr. Fusion 30, 1025), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In the present study, a 661-keV gamma ray was observed between the 3660-keV, 13/2 + state and one at 2998 keV; the latter may correspond to the one seen in Ref. [28]. The AD for this gamma ray is consistent with a ∆I = 1 dipole character [ Fig.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In the present study, a 661-keV gamma ray was observed between the 3660-keV, 13/2 + state and one at 2998 keV; the latter may correspond to the one seen in Ref. [28]. The AD for this gamma ray is consistent with a ∆I = 1 dipole character [ Fig.…”
Section: Discussionsupporting
confidence: 81%
“…12 of the (α, p) study by Nybø et al [28] there is an unlabelled peak Asai et al assigned firm spins and parities to all of the 67 Cu levels identified in Ref.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations